Start with assigning each person with a variable to represent their height
Ebi: e
Jose: j
Derell: d
Asami: a
Ebi'd height was 2.5 cm greater than Jose's height
j + 2.5 = e
Jose's height was 3.1 cm greater than Derell's
d + 3.1 = j
Derell's height is 0.4 cm less than Asami's height
a - 0.4 = d
Ebi is 162.5 cm tall
e = 162.5
So, plug in 162.5 into any of the above equations were there is a variable of e
j + 2.5 = e
j + 2.5 = 162.5
Subtract 2.5 from both sides of the equation
j = 160 cm
Jose's height is 160 cm
Now, plug in 160 into any of the above equations where there is a j
d + 3.1 = j
d + 3.1 = 160
Subtract 3.1 from both sides of the equation
d = 156.9 cm
Derell's height 156.9 cm
so, plug in 156.9 into any of the above equations where there is a d
a - 0.4 = d
a - 0.4 = 156.9
Add 0.4 on both sides of the equation
a = 157.3 cm
Asami's height is 157.3 cm
Hello,
(x-(-1+4i))(x-(-1-4i))=((x+1)-4i)((x+1+4i)
=((x+1)²+16
=x²+2x+17
Answer:
The exponent -9 makes the given statement true.
Step-by-step explanation:
We have been given an incomplete mathematical statement and we need to figure out the exponent for 5 on the right hand side to complete the statement.
The given incomplete statement is
.
Let us rewrite the left hand side of the expression by moving the exponential term to the numerator using exponent property. As per this property, if we shift an exponential term from denominator to numerator (or vice versa), the sign of exponent changes.
Therefore, we get:
![5^{-9}=5^{?}](https://tex.z-dn.net/?f=5%5E%7B-9%7D%3D5%5E%7B%3F%7D)
Now that we have common bases on both the sides, we can equate the exponents. And upon equating the exponents, we can see that the 'question mark' should be replaced by -9 in order for statement to be true.
Therefore, exponent -9 on the right hand side will make the statement true.
Answer:
![1008](https://tex.z-dn.net/?f=1008)
Step-by-step explanation:
When you multiply, always start on the first value. In this case, this would be 2 from 72.
![2 * 4](https://tex.z-dn.net/?f=2%20%2A%204)
![==> 8[tex]and[tex]2 * 1](https://tex.z-dn.net/?f=%3D%3D%3E%208%5Btex%5D%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3Eand%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%5Btex%5D2%20%2A%201)
![2](https://tex.z-dn.net/?f=2)
Write now, you should have 82 as your first value.
Now for your second value, which would be 7. But first you need to add a zero, because you are doing the tens place.
![7 * 4](https://tex.z-dn.net/?f=7%20%2A%204)
![==> 28](https://tex.z-dn.net/?f=%3D%3D%3E%2028)
<u>Now you put the two over your next equation:</u>
and
![7 * 1](https://tex.z-dn.net/?f=7%20%2A%201)
![==> 7](https://tex.z-dn.net/?f=%3D%3D%3E%207)
![+1](https://tex.z-dn.net/?f=%2B1)
![==> 9](https://tex.z-dn.net/?f=%3D%3D%3E%209)
Now you should have 980 written.
<u>Now add your two numbers together:</u>
<u></u>
![82 + 980](https://tex.z-dn.net/?f=82%20%2B%20980)
![==> 1008](https://tex.z-dn.net/?f=%3D%3D%3E%201008)
Answer:
Sphere
Solve for volume
V≈73622.18ft³
r Radius
26
ft
I don't know if that's right